Perfluorohexyloctane improves long-term storage of rat pancreata for subsequent islet isolation. - Brandhorst, H; Theisinger, B; Yamaya, H; Henriksnäs, J; Carlsson, P; Korsgren, O; Brandhorst, D (2009)
Pancreas oxygenation by means of the hyperoxygen carrier perfluorodecalin (PFD) has been established to prevent ischemically induced damage from cold-stored pancreata. However, large-scale studies did not confirm the promising results that had been observed in smaller donor populations. This study assessed whether islet isolation from pancreata stored for prolonged periods can be improved by utilizing the new oxygen carrier perfluorohexyloctane (F6H8) characterized by lower gravity and higher lipophilicity than PFD. Subsequent to 24 h of storage in either oxygenated PFD or F6H8, the rat pancreata were assessed for the intrapancreatic partial oxygen pressure (pO(2)) and subsequently processed with current standard procedures. The intrapancreatic pO(2) was nearly identical in rat pancreata stored either in PFD or F6H8. Nevertheless, rat islet isolation outcome was significantly increased in terms of yield, integrity, in vitro function and post-transplant outcome after transplantation in diabetic nude mice when F6H8 was used as oxygen carrier. This proof-of-concept study demonstrated in rats that islet isolation performed after long-term storage of oxygenated pancreatic tissue can be significantly improved if PFD was replaced by F6H8.